2D MoS2-polyurethane sponge for solar-to-thermal energy conversion in environmental applications: Crude oil recovery and seawater desalination. (June 2022) - Yoo, Changhyeon; Ko, Tae-Jun; Hwang, Jae-Hoon; Mofid, Sohrab Alex; Stoll, Stephanie; Osorto, Brandon; Morillo, Lody; Han, Sang Sub; Rodriguez, Kelsey L.; Lundin, Jeffrey G.; Lee, Woo Hyoung; Jung, Yeonwoong
Abstract: We developed two-dimensional (2D) molybdenum disulfide (MoS2 ) layers-incorporated polyurethane (PU) sponges and demonstrated their proficiency in various environmental applications. 2D MoS2 -PU sponges with precisely tailored porosity were fabricated by combining three-dimensional (3D) printing techniques and drop-casting of dispersed 2D MoS2 layers. The sponges exhibited excellent photothermal properties - i.e., rapid temperature increase under irradiation of photons - due to the high optical absorption property of the 2D MoS2 layers coupled with their intrinsic hydrophobicity. Such superior solar-to-thermal energy conversion was employed to demonstrate crude oil recovery and seawater desalination applications. It was observed that the sponges exhibited remarkably faster speeds in recovering crude oils where the sponges with 2D MoS2 layers resulted in complete recovery within 20 s under solar illumination vs. negligible recovery for the sponges without 2D MoS2 layers even up to 20 min. The sponges with 2D MoS2 layers also exhibited significantly higher evaporation rate (e.g., 3.5 kg m −2 h −1 ) in desalinating seawater with approximately 1.8 and 3.3 times higher evaporation rates for the sponges compared to those without 2D MoS2 layers and control (no sponge), respectively. This study provides a new pathway for the application of 2D MoS2 layer-based hierarchically structured porous materials in versatile and broad domains of environmental technologies. Graphical abstract: Unlabelled Image Highlights: 2D MoS2 sponges were fabricated by combining the 3D printing technique and the drop-casting of dispersed 2D MoS2 layers. Superior solar-to-thermal energy conversion of the 2D MoS2 sponges was employed for crude oil recovery and seawater desalination. 2D MoS2 sponges exhibit fast speed in recovering crude oils. 2D MoS2 sponges exhibit high evaporation rates in desalinating seawater.